MAPPING OF SCIENTIFIC PUBLICATIONS ON LIBRARIES AND THE SUSTAINABLE DEVELOPMENT GOALS (SDGs): A BIBLIOMETRIC ANALYSIS - gema; Triandari, Rizki (LIBRIA, 2025)
This study explores the scientific literature that examines the role of libraries in implementing the Sustainable Development Goals (SDGs). Using a bibliometric approach, the dataset comprises 1,152 publications indexed in Scopus from 2016 to 2024, analyzed with VOSviewer software. The results reveal a growing trend in publications, particularly between 2020 and 2024. The most productive countries are the United States, India, and Nigeria, while the most influential journals include Emerald Emerging Markets Case Studies, Sustainability (Switzerland), and Library Philosophy and Practice. The most frequently cited articles focus on themes such as cultural sustainability, public libraries, digital inclusion, and open access. Co-occurrence analysis produced seven thematic clusters, encompassing areas such as information management, academic innovation, and information literacy. Overlay and density visualizations indicate a thematic shift from digital infrastructure to more contextual topics, including green libraries and community engagement. These findings affirm the position of Library as a social science discipline that contributes to sustainable development. In addition, these findings are expected to provide an empirical foundation for future research agendas.